Triazine-based covalent organic polymer as stable luminescent probe for highly selective detection of 2, 4, 6-trinitrophenol. (August 2021) - Zhuang, Yan; Shan, Houchao; Zhang, Zepeng; Li, Shufeng; Zhu, Qian; Si, Zhihao; Yang, Shuai; Yang, Zhen; Cai, Di; Qin, Peiyong
Abstract: In this work, in order to highly selective detection of aromatic nitro-compounds, novel triazine-based covalent organic polymer named TTRZ was designed and synthesized through Schiff base reaction between triazine-containing monomer and terephthalaldehyde, and was applied as the luminescent probe. The as-synthesized nanoparticles were characterized by BET, FTIR, TGA, XRD, SEM and TEM. Owing to the extended π conjugated structure, the TTRZ nanoparticles possessed strong fluorescence intensity, which further facilitates high sensitivity to the aromatic nitro-compounds. Attractively, the Ksv value for 2, 4, 6-trinitrophenol (TNP) can be reached to 1.15 × 10 5  M −1, while the detection limit of TNP was only 27 ppb. The mechanism of quenching effect of TTRZ by TNP was also clarified, which was ascribed to the dynamic quenching, electron and energy transfer. Furthermore, cellulose acetate film that incorporating with TTRZ was prepared for TNP detection. As expect, significant fluorescence quenching was achieved after dropping the TNP solution on the surface of film, suggesting that TTRZ is an excellent candidate for the detection of aromatic nitro-compounds. Highlights: TTRZ were synthesized as fluorescent probes to detect aromatic nitro-compounds. TTRZ exhibited excellent sensitivity and selectivity on TNP with fast response. The cellulose acetate film was applied for fluorescence detection. Mechanism of quenching effect of TTRZ by aromatic nitro-compounds was clarified.